Dibromido(6,6′-dimethyl-2,2′-bipyridine-κ2N,N′)cadmium - Sadif A. Shirvan; Sara Haydari Dezfuli (Acta Crystallographica Section E, 2012)
In the title compound, [CdBr2(C12H12N2)], the CdII atom is four-coordinated in a distorted tetrahedral geometry by two N atoms from a 6,6′-dimethyl-2,2′-bipyridine ligand and two terminal Br atoms. In the crystal, C—H...Br hydrogen bonds and π–π stacking interactions between the pyridine rings [centroid–centroid distance = 3.763 (5) Å] are present.